AB0982 Prevalence of osteoarthritis in high altitude area of tibet. (12th June 2018) - Liang, Y.; Mei, Y.; Guan, S.; Sun, W.; Wang, W.; Teng, F.; Han, X.; Zhang, Z.
Abstract : Background: Osteoarthritis is a degenerative joint disease; the specific etiology and pathogenesis are unclear. The prevalence of osteoarthritis of subtypes of joints is different, whereas the most common osteoarthritis occurs in knees. In China, the prevalence of osteoarthritis is about 15%, the prevalence of the patients over 40 years old is 10% 17%, and 50% over the age of 60, while over 75 years old was as high as 80%. Few data exist regarding the prevalence of OA in plateau in China. Objectives: To investigate the prevalence of osteoarthritis(OA) in Jiuhe village, which is located about 3.5 kilometres high of Qonggyai County of Tibet and the associated factors in order to provide the guidance for the prevention and treatment of OA. Methods: The participants in this analysis were all the resident people aged 50 years and above in Jiuhe village, Qonggyai County of Tibet. All subjects were invited to completed an questionnaire, physical examination and radiographic examination. The questionnaire included sex, age, body mass index(BMI) and dietary habit. Results: A total of 136 participants aged 50–86 years were enrolled, including 47 males with mean age of 62.00±9.11 years, and 89 females with mean age of 61.30±9.52 years. Altogether 102 knee OA can be diagnosed, the total prevalence of knee OA was 75.00%. Knee OA occurred in 78.72% of male and 73.03% of female. The prevalence of knee OA combined with hand OA was 19.12%, and 21.28% for male and 17.98% for female. The prevalence of knee OA combined with hand OA increased with age in the female, no such trend was observed in male or in only knee OA patients. No significant difference was found about sex, BMI, drinking between the OA patients and the controls. Conclusions: The prevalence of osteoarthritis in Jiuhe village, plateau of Tibet was significantly high. The prevalence in male is higher than that in female. The prevalence of knee OA combined with hand OA increased with age in the female. Acknowledgements: Create China Hearts Foundation Disclosure of Interest: None declared